Filling the Jurisprudential Gap: “Regular and Established Place of Business” After In Re Cray, Inc. - David A. Serati (Washington University Law Review, 2018)
Since the nineteenth century, specific venue rules for patent infringement suits have existed in federal law. The current version of the “Patent Venue Statute” is codified in 28 U.S.C. § 1400(b), which provides that “[a]ny civil action for patent infringement may be brought in the judicial district where the defendant resides, or where the defendant has committed acts of infringement and has a regular and established place of business.” Over time, the reach of this statute has changed in relation to where a corporation “resides” in the specific context of the statute. These changes have come when courts interpret the relationship between the Patent Venue Statute and amendments to the “General Venue Statute.” In TC Heartland, LLC v. Kraft Goods Grp. Brands, LLC, the Supreme Court yet again changed our understanding of the relationship between the General Venue Statute and the Patent Venue Statute, upending over thirty years of precedent by holding that the narrower Patent Venue Statute jurisprudence, not the General Venue Statute, determines the meaning of the word “resides.” However, the TC Heartland Court provided no guidance on how to apply the second portion of this once-extinct rule of civil procedure. This Note aims to provide some of that missing guidance necessary to determine which precedent remains good law, which case law has been expressly or implicitly overruled, and how the Court of Appeals for the Federal Circuit (Federal Circuit) and federal district courts are likely to rule in novel factual situations moving forward. The determinative issue in the vast majority of patent venue decisions is whether the defendant has a “regular and established place of business” in the federal judicial district where a plaintiff brings suit. Venue is important to litigants because the local rules of each district court can vary drastically, and these rules influence the length of the proceeding, the jury pool, the cost of litigation, and the likelihood of success. In In re Cray, Inc., the Federal Circuit articulated a new legal test for applying the Patent Venue Statute to different factual scenarios to answer whether there is a regular and established place of business in a plaintiff’s desired judicial district. In Cray, a defendant’s sales employee conducted some business activities from his home in the Eastern District of Texas. In holding that there was no regular and established place of business—thereby making venue improper—the Federal Circuit recited three elements necessary to satisfy the regular and established place of business requirement: (1) there must be a “fixed, physical location,” (2) the location must be a “regular and established place of business,” and (3) the location must be “of the defendant.” These requirements overruled the four-factor test Judge Gilstrap articulated in the proceeding below in the Eastern District of Texas. Since the alleged facts did not establish that the defendant had any ownership or possessory interest in the employee’s residence, the physical location in the district did not belong to the defendant, and the third requirement was not met. This Note argues that the Federal Circuit’s interpretation of the Patent Venue Statute is consistent with Congress’s original purpose for enacting it, which was to narrow the scope of venue when compared to general venue requirements. Where Cray conflicts with prior case law, it conflicts only to the extent that there was already a conflict in the precedent with this original purpose. And in most decisions after Cray, district courts have resolved the conflict on the side of a narrower reading that would find venue improper. In other words, federal district court cases applying Cray’s legal test have similarly erred on the side of a narrow reading. Even though there will surely be much more case law on this topic, Cray provides a roadmap for the factual scenarios likely to trigger a venue challenge worth litigating, and thus require a court’s analysis.
Keywords: Patent Law; 28 USC 1400; 1400(b); regular and established place of business; patent law; intellectual property law; venue; general venue statute; patent venue statute; Cray; In re Cray; TC Heartland; 871 F.3d 1355 (2017); traveling salesman; sales office; parent and subsidiary corporation; independent sales representative; federal circuit; CAFC